2008
DOI: 10.1016/j.jviromet.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection of small ruminant lentiviral nucleic acid sequences located in the proviral long terminal repeat and leader-gag regions using real-time polymerase chain reaction

Abstract: Real-time polymerase chain reaction (RT-PCR) detection of proviral nucleic acid sequences of small ruminant lentiviruses (SRLV) in blood samples was developed and evaluated.Priming oligonucleotides were designed on the highly conserved 5 untranslated leader-gag region while those on the long terminal repeat (LTR) assay were derived from literature. DNA was extracted from the buffycoat interlayer of centrifuged blood samples. Real-time PCR was performed by means of LightCycler technology (Roche Applied Science)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
1
30
0
6
Order By: Relevance
“…The PCR method probably gave zero false negatives and had the possibility for diagnosis of CAEV infection by detecting proviral sequences when antibody is absent in circumstances of early infection prior to seroconversion. On the other hand, PCR assay is very useful to prove viral infection in seropositive kids which received maternal antibody from their dams (de Andres et al 2005, Brinkhof et al 2008. When considering the test performance of ELISA, we found satisfactory results as also described by de Andres et al (2005), that the sensitivity values ranged from 92 to 100%.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The PCR method probably gave zero false negatives and had the possibility for diagnosis of CAEV infection by detecting proviral sequences when antibody is absent in circumstances of early infection prior to seroconversion. On the other hand, PCR assay is very useful to prove viral infection in seropositive kids which received maternal antibody from their dams (de Andres et al 2005, Brinkhof et al 2008. When considering the test performance of ELISA, we found satisfactory results as also described by de Andres et al (2005), that the sensitivity values ranged from 92 to 100%.…”
Section: Discussionsupporting
confidence: 64%
“…This finding suggested that in any disease circumstance, ELISA has a possibility of around 95% to detect the truly infected goats and has a possibility of around 83% to indicate the healthy goats. This result depended on the sensitivity that might be caused by the fluctuation of antibody response after infection as well as on the disease prevalence (de Andres et al 2005, Thrusfield 2007, Brinkhof et al 2008 In this study, a relatively high specificity of PCR was expected (Reddy et al 1993, Rimstad et al 1993, Wagter et al 1998, Celer et al 2000, Extramiana et al 2002. This indicated a suitable performance used as a confirmatory test.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Thus, the development of qPCR in this study was followed by genotyping of SRLV strains isolated from infected ewes. Using degenerative primers specific for subtype A12, which is typical for Polish isolates of SRLV, the newly developed qPCR showed high specificity and sensitivity, comparable to those noted for other qPCR assays developed for detection of SRLV infection (5,17). There was a positive correlation between the number of lambs which were positive by qPCR and gag nested PCR at 12 weeks after the birth; however, none of the samples was positive when tested by env nested PCR.…”
Section: Discussionmentioning
confidence: 63%
“…The development of fluorescent methods for PCR and also the instruments like real-time which can monitor the amplification process is considered as a significant improvement in molecular biology. qPCR have been extensively used in various branches of life sciences during the past few years, which includes infectious disease detection in humans (Enbom et al, 2001), animals (Brinkhof et al, 2008) and plants (Boonham et al, 2004), Sample size PCR for TYLCV-OM S0 10 -S1 10 + S2 10 + S3 10 + The (+) sign indicates detection of the virus while the (-) sign indicates that the virus was not detected using PCR (Papayiannis et al, 2009) and mutation scanning (Wittwer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%